Targeting T Cell Metabolism for Improvement of Cancer Immunotherapy - Le Bourgeois, Thibault; Strauss, Laura; Aksoylar, Halil-Ibrahim; Daneshmandi, Saeed; Seth, Pankaj; Patsoukis, Nikolaos; Boussiotis, Vassiliki A. (Frontiers in Oncology, 2018)
There has been significant progress in utilizing our immune system against cancer, mainly by checkpoint blockade and T cell-mediated therapies. The field of cancer immunotherapy is growing rapidly but durable clinical benefits occur only in a small subset of responding patients. It is currently recognized that cancer creates a suppressive metabolic microenvironment, which contributes to ineffective immune function. Metabolism is a common cellular feature, and although there has been significant progress in understanding the detrimental role of metabolic changes of the tumor microenvironment in immune cells, there is still much to be learned regarding unique targetable pathways. Elucidation of cancer and immune cell metabolic profiles is critical for identifying mechanisms that regulate metabolic reprograming within the tumor microenvironment. Metabolic targets that mediate immunosuppression and are fundamental in sustaining tumor growth can be exploited therapeutically for the development of approaches to increase the efficacy of immunotherapies. Here, we will highlight the importance of metabolism on the function of tumor-associated immune cells and will address the role of key metabolic determinants that might be targets of therapeutic intervention for improvement of tumor immunotherapies.